Chemical modification of polysaccharides with hydrophilic polymers for CaCO3 crystal growth modification and filler retention, for paper applications - Matahwa, Howard (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Chemistry and Polymer Science))--Stellenbosch University, 2008.